Cyclocarya paliurus leaves extracts alleviate metabolic phenotypes in Chinese T2DM patients by modulating gut microbiota and metabolites: a clinical randomized controlled trial - Peng, Xiaojuan; Chen, Sisi; Zhong, Lu; Li, Yuting; Wu, Chutian; Zhong, Lixian; Chen, Weiwei; Yang, Jinying; Zeng, Jiahua; Tang, Shaohui (Frontiers in Endocrinology, 2023)
Abstract Objective We aimed to investigate the effect of Cyclocarya paliurus leaves extracts (CP) on glucolipid metabolism and its relationship with intestinal flora in T2DM patients. Methods In this open-label, 84-day randomized controlled trial, a total of 38 T2DM patients were randomly assigned to the CP group or the Glipizide group (G group) in a 2:1 ratio. T2DM-associated metabolic phenotypes, gut microbiota and metabolites including SCFAs and BAs were detected. Results At the end of intervention, CP, like Glipizide, significantly improved HbA1c level and other glucose metabolism parameters (FBG, 2hPBG, OGTT glucose AUC). Moreover, CP also resulted in the significant improvement in the levels of blood lipid and blood pressure. Notably, the improvement in blood lipid (TG and HDL-c) and blood pressure (DBP) was significantly greater in the CP group compared with the G group. Furthermore, the liver and kidney function parameters did not significantly change in both CP group and the G group over the 84-day period. Additionally, the enrichment of potentially beneficial bacteria (Faecalibacterium and Akkermansia), SCFAs and unconjugated bile acids (BAs) and the depletion of potential pathogenic bacteria (Prevotella_9) and conjugated BAs were observed in the CP group, while the abundances of the gut microbial were kept stable in the G group after intervention. Conclusion CP displays a more beneficial effect in the alleviation of T2DM-associated metabolic phenotypes than glipizide by regulating gut microbiota and metabolites in T2DM patients, with no significant effects on liver and kidney function.